REKONSEPTUALISASI PENGATURAN PENGADAAN BARANG DAN JASA PEMERINTAH DALAM KAITANNYA DENGAN TINDAK PIDANA KORUPSI.1 - Mexsasai Indra (Fakultas Hukum Universitas Riau, 2015)
Regulations was publishedrelating to governmentprocurement of goods andservices intended for theprocurement of goods andservices more perfect and reducethe adverse of deviation statefinances. In the procurement ofgoods / services of governmentagencies, there are three areas oflaw that directly and indirectlyregulate the procurement ofgoods / services, they are theState Administration Law, Civiland Criminal. When linked withthe provisions of the acts ofcorruption stipulated in Law No.31 1999 Junto Law 20 of 2001.So, if examined will be foundsome elements including:unlawful, enrich themselves inthe procurement of goods /services.